2008
DOI: 10.1016/j.neuroscience.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampal region of rats and mice after a single i.p. dose of clioquinol: Loss of synaptic zinc, cell death and c-Fos induction

Abstract: Clioquinol (CQ) is able to chelate synaptic zinc, which can modulate excitatory and inhibitory neurotransmission. In humans, CQ was associated with cases of transient global amnesia (TGA) and with the neurodegenerative syndrome subacute myelo-optico-neuropathy (SMON). We examined the CQ induced loss of synaptic zinc, cell death and c-Fos induction in rats and mice. In rats, we found a strong reduction of histochemically reactive synaptic zinc no later than 4 h after the injection of the lowest dose of CQ (50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 101 publications
(103 reference statements)
1
5
0
Order By: Relevance
“…route is highly effective in reducing the pool of chelatable Zn 2+ in the brain and the hippocampus in particular 33,39 . In agreement with previous studies [33][34][35][36][37][38] , we obtained a significant decrease of hippocampal Zn 2+ levels (Supplementary fig. 1; normalized TSQ fluorescence in control: 1.00±0.08 vs 0.49±0.04 in CQ-treated mice, p<0.001).…”
Section: Cq Administration Impairs Learning Short-and Long-term Memosupporting
confidence: 93%
See 1 more Smart Citation
“…route is highly effective in reducing the pool of chelatable Zn 2+ in the brain and the hippocampus in particular 33,39 . In agreement with previous studies [33][34][35][36][37][38] , we obtained a significant decrease of hippocampal Zn 2+ levels (Supplementary fig. 1; normalized TSQ fluorescence in control: 1.00±0.08 vs 0.49±0.04 in CQ-treated mice, p<0.001).…”
Section: Cq Administration Impairs Learning Short-and Long-term Memosupporting
confidence: 93%
“…In this study, we investigated the cognitive effects of Zn 2+ chelation in young mice. Previous studies have shown that intraperitoneal CQ administration promotes a robust reduction of the pool of chelatable Zn 2+ in rodents [33][34][35][36][37][38] . The main finding of the study is that a 2-week administration of CQ exerts adverse effects on learning and memory performances of treated mice.…”
Section: Discussionmentioning
confidence: 97%
“…Cell death is observed in the dentate granule cell layer 24 h after i.p. injection of CQ (100 mg/kg) into mice, while there is no evidence of cell death for any dose (50–200 mg/kg) and up 1 week after CQ injections into rats (Ismail et al, ). Thus CQ‐induced cell death may not occur in the dentate gyrus of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the antibiotic/zinc chelator Clioquinol have revealed an association with this zinc chelating agent and transient global amnesia and neurodegenerative disorders [51]. In related areas of neurobiology, studies on Alzheimer diseased brains have shown a rather deleterious effect when removing zinc from the diet, with a subsequently increased plaque load especially in the neocortex which contains high amounts of ZEN neurons [52].…”
Section: Discussionmentioning
confidence: 99%